Evaluation of Performance Appraisal Instrument Development for Nurse Based On Self Efficacy at Lavalette Hospital in Malang - Rahayu Tri Nuritasari; Rizki Fitriyasari; M Hasinuddin (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Performance appraisal is problematic if it does not describe competence. Design of the research was explorative descriptive research with a research and development approach. The sample was 110 nurses obtained by cluster sampling based on inclusion criteria. Data were then analyzed using descriptive analysis. Development of instruments based on Focus Group Discussion and expert discussion. The result show evaluation of components in the nurse performance appraisal system when viewed according to its indicators, most are rated in the sufficient category. Assessment criteria and performance records get enough categories in the highest percentage of 76.4%, evaluation of the standard components of work behavior assessment is mostly not done with percentages above 20%, performance appraisal instruments do not describe the performance of nurses and do not conform to standards.